The Pharmacological Burden of Comorbidities in Acromegaly - Fleseriu, Maria (J Endocr Soc, 2021)
Background: Acromegaly is characterized by excess GH and elevated IGF-I often treated by surgery, pharmacotherapy (somatostatin analogs, GH receptor antagonists, dopamine agonists) and/or radiotherapy.(1) Common associated comorbidities include cardiovascular disorders and hypopituitarism, often requiring additional pharmacotherapy.(2) We therefore assessed the most common comorbidities and related pharmacological burden in patients with acromegaly in a real-world clinical setting. Methods: The MarketScan database was examined for medical claims from Jan 2010 to Jan 2020. We defined 2 groups: Group 1 - patients with acromegaly (2 diagnoses [ICD-9-CM/ICD-10-CM] on dates within >30 days) who had ≥1 medication for acromegaly since diagnosis, with ≥3 months coverage prior to index date (diagnosis date or first treatment available); Group 2 - a matched cohort (MC) with no acromegaly-related medical claims; direct matching (1:5 based on age, sex and follow-up duration) was performed. Group proportions and quantitative differences were compared by chi-squared tests and t-tests, respectively (unpaired due to different cohort sizes). Results: 1,175 patients with and 5,875 without acromegaly were analyzed. Across both groups, median (95% CI) age was 50 (49, 51) years, 50% were female, median (95% CI) follow-up was 751 (702, 805) days. Comorbidities reported in ≥20% patients with acromegaly vs the MC were cardiovascular system disorders (68% vs 48%), hypopituitarism/hypothalamic disorders (26% vs 0%), sleep apnea (25% vs 8%), malignant neoplasms (23% vs 9%), arthritis and muscular skeletal disorders (20% vs 13%); frequencies were significantly higher in patients with acromegaly vs the MC (all p<0.0001). Thyroid replacement, lipid modifying and renin-angiotensin system agents were the most common treatments related to these comorbidities, all used more frequently in acromegaly (35%, 34% and 34%, respectively) vs the MC (9%, 26% and 25%, respectively; all p<0.0001). Overall in patients with acromegaly vs the MC, mean (SD) number of different oral medications used was 12.01 (10.49) vs 7.21 (7.99); 5% vs 20% and 79% vs 58% took 0 and ≥3 oral medications, respectively (all comparisons p<0.0001). Significantly more patients with acromegaly vs the MC took medications typically taken while fasting e.g. levothyroxine (34% vs 9%) and omeprazole (14% vs 9%), both p<0.01. Conclusions: In this real-world analysis, patients with acromegaly had more comorbidities, compared with a matched population and required many concomitant medications. Oral medication use with or without fasting was higher in patients with acromegaly. These findings elucidate further physician understanding of the pharmacological burden of acromegaly comorbidities. Funding: This ongoing study is sponsored by Ipsen. 1.Katznelson L J Clin Endocrinol Metab 2014:99:3933-51 2.Gadelha M Endocr Rev 2019:40:268-332